(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article presents the results of scientific and economic experience in studying the reserves for increasing the meat productivity of cattle calves during fattening.It has been established that the mineral and vitamin supplements introduced into the diet of cattle calves during fattening improve the digestibility of nutrients in the eaten feed, increase the formation of meat productivity and daily increase in live weight, as well as the effectiveness of farming technology.